Digital Financial Assets: Problems of Recognition, Valuation and Legal Regulation in Accounting - PYLYPENKOО.; YURCHENKOО. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
The article reveals the author’s vision of the recognition, valuation and legal regulation of accounting of digital assets at company level. The economic nature of cryptocurrency is discussed through interpreting the functions of money: a measure of value, a means of circulation, a means payment and accumulation, and the global money. It is concluded that cryptocurrency does not comply with the classical definition of “money”, because it does not feature its main functions. But it can be said that cryptocurrency constitutes the first opened, digital alternative currency able to take the form of traditional money. The procedure for cryptocurrency valuation in the business stocks and intangible assets is analyzed. In cases when a business entity is intended to buy cryptocurrency as a commodity, the transactions related to cryptocurrency flows should be recorded on the account 28 “Commodities”, whereas the transactions related to cryptocurrency production should be recorded on the account 26 “Finished products”. The proposed improvements in cryptocurrency accounting in the company stocks will be realizable when the transactions on cryptocurrency purchase or production (mining) are performed on permanent basis. The recognition of cryptocurrency in the intangible assets of a company will be feasible on the following conditions: cryptocurrency does not have a physical form; it can be identified; it is a non-monetary asset. The distinctive features of Bitcoin in relation to financial instruments are outlined, ways of cryptocurrency production using ІСО, mining, forging etc. are discussed. Regarding the legal regulation of cryptocurrency circulation in Ukraine, it is revealed that no normative and legal document exists to specify the legal status of the notions “virtual assets”, “digital financial assets” or “cryptocurrency”. By now, the draft law has been approved, intended to regulate purchase, sale and taxation of virtual assets. The official recognition of digital financial assets and blockchain technology is expected to promote the transition of Ukraine to the digital economy. This transition is going to give rise to the emergence of a new object of accounting, e. g. digital financial assets. The authors’ vision of the normative and legal regulation of cryptocurrency accounting at micro- and macrolevel allowed to propose a new national standard of accounting “Digital financial assets”, to develop a methodological framework for reporting the data on digital financial assets and their disclosure in the financial statements of companies.